Evaluasi Etos Kerja Karyawan Di PT. Jasaraharja Putera Cabang Bengkulu - Saputra, Harius Eko; Imanda, Antonio; Aprilia, Wulan (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to evaluate the work ethic of employees at PT. Jasaraharja Putera Bengkulu Branch and identify the factors influencing it. Work ethic refers to the attitudes, values, and behaviors exhibited by individuals in performing their duties, directly affecting the performance and service quality of the organization. A quantitative method was employed, using a survey approach with 55 respondents who are active motor vehicle insurance (JP-ASTOR) customers. Data were collected through questionnaires designed based on indicators of work ethic and service quality. The research findings indicate that the employees demonstrate a relatively high level of work ethic, especially in terms of discipline, responsibility, and adaptability to the implemented management information system. However, some limitations were observed regarding their comprehension and optimal use of information technology. A simple linear regression analysis reveals a positive and significant influence between the management information system and service quality. These results imply that strengthening employee work ethics through training in information technology and system usage can enhance the competitiveness of financial service companies like PT. Jasaraharja Putera.This research offers theoretical contributions to the development of human resource management in the insurance service sector and serves as a strategic reference for internal policy decisions aimed at improving service effectiveness and customer satisfaction.